Pengaruh Peran Media Sosial pada Himpunan Bisnis Digital Universitas Nasional dalam Budaya Musyawarah dan Mufakat - Marsha Nur Aisyah; Nabila Dwi Irwanti; Olivia Roza; Alysa Careva Putri; Zeira Azzuria; Qudsy Adha Aulia; Rashya Cika Wardani; Mochdar Soleman (Jurnal Pendidikan dan Kewarganegara Indonesia, 2026)
The development of social media has transformed communication patterns within student organizations, including the practice of deliberation and consensus-building as the basis for decision-making. This study aims to analyze the influence of social media on the culture of deliberation and consensus-building within the National University Digital Business Student Association. The study employs a qualitative method with a descriptive approach through interviews with ten informants selected using purposive sampling. The data were analyzed using the Miles and Huberman model. The results show that social media—particularly WhatsApp, Discord, and Zoom—play a crucial role in supporting coordination, information dissemination, and the rapid and flexible making of technical decisions. However, face-to-face deliberations are still considered more effective for discussing complex issues because they minimize miscommunication, increase member participation, and facilitate the achievement of consensus. This study concludes that social media serves as a tool to support organizational communication but has not yet been able to replace the role of face-to-face deliberation. Therefore, a more structured framework for the use of social media is needed to ensure that the effectiveness of digital communication remains aligned with the values of deliberation and consensus within student organizations.